2021
DOI: 10.1111/eva.13301
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics linked to glacial cycles in Cercis chuniana F. P. Metcalf (Fabaceae) endemic to the montane regions of subtropical China

Abstract: The mountains of subtropical China are an excellent system for investigating the processes driving the geographical distribution of biodiversity and radiation of plant populations in response to Pleistocene climate fluctuations. How the major mountain ranges in subtropical China have affected the evolution of plant species in the subtropical evergreen broadleaved forest is an issue with long‐term concern. Here, we focused on Cercis chuniana, a woody species endemic to the southern mountain ranges in subtropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 160 publications
(191 reference statements)
1
3
0
Order By: Relevance
“…Previous studies have reported the existence of multiple refugia during the Quaternary ice age in this region [62]. The presence of these refugia facilitated the divergence of surviving species through long-distance isolation [12,63]. Additionally, we found that distinct haplotypes of these four species successively emerged during the Pleistocene (Fig.…”
Section: Demographic History Of the G Crenulata Groupsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies have reported the existence of multiple refugia during the Quaternary ice age in this region [62]. The presence of these refugia facilitated the divergence of surviving species through long-distance isolation [12,63]. Additionally, we found that distinct haplotypes of these four species successively emerged during the Pleistocene (Fig.…”
Section: Demographic History Of the G Crenulata Groupsupporting
confidence: 64%
“…They have been posited to decrease biodiversity [10], yet also have been thought to serve as biodiversity reservoirs [11]. Research on these forests has predominantly focused on ecosystem stability, species composition, and community/stand structure for ecosystem restoration [10,12]. Less emphasis has been placed on adaptation to disturbance and successional dynamics of pioneer species in this ecosystem, particularly within the context of phylogeography at a geological scale.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the geographical distance and genetic divergence of F. hirta populations were further supported by an IBD analysis with Mantel test ( R 2 = 0.281, P < 0.001). This may be related to the geographical isolation barrier of Luoxiao Mountains and Nanling Mountains between the mid-south and northeast populations, diminishing the gene flow between the above two clusters (which can also be found in other species like Gynostemma pentaphyllum [ 21 ], Eomecon chionantha [ 31 ] and Cercis chuniana [ 32 ]. Although there was a significant IBD patterns of F. hirta , we found a relatively low genetic differentiation in F. hirta ( G’ ST = 0.147) (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the diverse topography and ecology, this region has long been regarded as a global hotspot of biodiversity (López‐Pujol et al., 2011 ). These characteristics make Southwest China an excellent system for studying processes that drive the geographical distribution of biodiversity (Liu et al., 2021 ). One important question is whether genetic differentiation is driven by complete geographical isolation or by environmental selection.…”
Section: Introductionmentioning
confidence: 99%